2017
DOI: 10.1074/jbc.m116.723700
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Activation of Glutamate Cysteine Ligase with Dimercaprol

Abstract: Edited by F. Anne StephensonNeuroinflammation and oxidative stress are hallmarks of various neurological diseases. However, whether and how the redox processes control neuroinflammation is incompletely understood. We hypothesized that increasing cellular glutathione (GSH) levels would inhibit neuroinflammation. A series of thiol compounds were identified to elevate cellular GSH levels by a novel approach (i.e. post-translational activation of glutamate cysteine ligase (GCL), the rate-limiting enzyme in GSH bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…As a result, agmatine increases total glutathione content in non-activated and activated microglia. In line with this, increased GSH content in BV-2 cells is associated with protection against Lps-induced activation [ 75 ].…”
Section: Discussionmentioning
confidence: 79%
“…As a result, agmatine increases total glutathione content in non-activated and activated microglia. In line with this, increased GSH content in BV-2 cells is associated with protection against Lps-induced activation [ 75 ].…”
Section: Discussionmentioning
confidence: 79%
“…Using a transglycosylation reaction, it was discovered that chitinase isolated from Trichoderma reesei KDR-11 transforms (GlcNAc) 4 to (GlcNAc) 2 (55.7%) and (GlcNAc) (39.6%) [55]. COS with DP 4-12 were successfully generated using a lysozymecatalyzed transglycosylation reaction with N,N′,N″-tri (monochloro) acetylchitotriose and N,N′,N″-triacetylchitotriose as substrates, followed by a base-catalyzed removal technique to remove the N-monochloroacetyl groups [56,57].…”
Section: Extraction Of Chitin Oligosaccharidesmentioning
confidence: 99%
“…Although that is not what we observed in this study, there is evidence that Nrf2 targets can be post-transcriptionally activated, independent of the expression levels of their target molecules. McElroy et al reported post-transcriptional activation of GCL with no effects on the expression of Nrf2 and other target molecules [57,58].…”
Section: Discussionmentioning
confidence: 99%